2018
DOI: 10.1111/cei.13153
|View full text |Cite
|
Sign up to set email alerts
|

HE4 suppresses the expression of osteopontin in mononuclear cells and compromises their cytotoxicity against ovarian cancer cells

Abstract: Ovarian cancers are known to evade immunosurveillance and to orchestrate a suppressive immune microenvironment. Here we examine the role of human epididymis protein 4 (HE4), an ovarian cancer biomarker, in immune evasion. Through modified subtractive hybridization analyses we have characterized the gene targets of HE4 in human peripheral blood mononuclear cells (PBMCs), and established a preliminary mechanism for HE4-mediated immune failure in ovarian tumours. Upon exposure of purified PMBCs to HE4, osteoponti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Immunohistochemical staining of an ovarian cancer microarray (US Biomax, OV802a) was performed as previously described [50], using antibodies for HE4 (Santa Cruz, sc-293473) and DUSP6 (MyBioSource, MBS8516662). Confocal microscopy was performed by an independent imaging technician at the Rhode Island Hospital Digital Imaging Core Facility with a Nikon C1si confocal (Nikon Inc. Mellville, NY, USA).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Immunohistochemical staining of an ovarian cancer microarray (US Biomax, OV802a) was performed as previously described [50], using antibodies for HE4 (Santa Cruz, sc-293473) and DUSP6 (MyBioSource, MBS8516662). Confocal microscopy was performed by an independent imaging technician at the Rhode Island Hospital Digital Imaging Core Facility with a Nikon C1si confocal (Nikon Inc. Mellville, NY, USA).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…In recent years, a growing number of investigations have gradually found that HE4 promotes cell proliferation, adhesion, invasion, migration, and chemoresistance in ovarian cancer [20][21][22][23][24][25][26][42][43][44][45][46][47]. It was found that HE4 overexpression or rHE4 treatment in EOC cells resulted in upregulation of many transcripts coding for extracellular matrix proteins, including LAMC2, LAMB3, SERPINB2 and GREM1; moreover, in cells overexpressing HE4 or exposed to rHE4 in culture medium, the protein levels of LAMC2 and LAMB3 were continously increased, and in the presence of bronectin, the focal adhesions were elevated in cells treated with rHE4 [22].…”
Section: Discussionmentioning
confidence: 99%
“…It was known that ovarian cancer participates in evading immunosurveillance and orchestrating a suppressive immune microenvironment, a series of studies by James NE, et al [23,44,45] found that, upon exposure of puri ed human peripheral blood mononuclear cells(PBMCs) to HE4, osteopontin (OPN) and DUSP6 appeared as the most inhibited and upregulated genes; the proliferation of human ovarian carcinoma cells in conditioned media from HE4-exposed PBMCs was enhanced, while the effect was attenuated by adding recombinant OPN or OPN-inducible cytokines (IL-12 and IFN-γ); HE4 can compromise both OPN-mediated T cell activation [44] and cytotoxic CD8 + /CD56 + cells through upregulation of self-produced DUSP6 [45], thus promoting the tumorigenesis of ovarian cancer [23,44,45,48]. Other researchers found that HE4 promotes carcinogenesis of ovarian cancer by combining with histone deacetylase 3 (HDAC3) to activate PI3K/AKT pathway [46], and that HE4 knockdown suppresses the invasive cell growth and malignant progress of ovarian cancer by inhibiting JAK/STAT3 pathway [24].…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer participates in the evasion of immunosurveillance and orchestrates a suppressive immune microenvironment. A series of studies by James et al [23,44,45] showed that upon exposure of puri ed human peripheral blood mononuclear cells to HE4, osteopontin (OPN) and DUSP6 were the most downregulated and upregulated genes, respectively. The proliferation of human ovarian carcinoma cells in conditioned media from HE4exposed peripheral blood mononuclear cells was enhanced, whereas this effect was attenuated by adding recombinant OPN or OPN-inducible cytokines (interleukin-12 and interferon-γ).…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation of human ovarian carcinoma cells in conditioned media from HE4exposed peripheral blood mononuclear cells was enhanced, whereas this effect was attenuated by adding recombinant OPN or OPN-inducible cytokines (interleukin-12 and interferon-γ). HE4 can compromise both OPN-mediated T cell activation [44] and the activity of cytotoxic CD8 + /CD56 + cells by upregulating self-produced DUSP6 [45], thus promoting the tumorigenesis of ovarian cancer [23,44,45,48]. Other researchers revealed that HE4…”
Section: Discussionmentioning
confidence: 99%